Staying and concluding higher education: What Indians say about the Universidade Estadual do Centro-Oeste do Paraná [UNICENTRO] – Brazil - Angnes, Juliane Sachser; Freitas, Maria de Fátima Quintal de; Klozovski, Marcel Luciano; Costa, Zoraide da Fonseca; Rocha, Carla Marlana (Education Policy Analysis Archives, 2017)
This article aims to understand the perspective of indigenous students, about staying and completing their studies at Universidade Estadual do Centro-Oeste do Paraná [UNICENTRO] - Brazil, considering the experience of the Special Entrance Examination for Indigenous Peoples in this state. This is a qualitative research, accomplished from 2002 to 2010, in order to listen to the Indians voices (and silence), and their difficulties to complete higher education. The results showed that, this process regarded as an “inclusion of Indians at the university” –a secular and privileged space– is restricted to access. That is, the psychosocial effect generated by the false idea that a supplemental program of vacancies is distorting, as it creates a false notion that society is becoming more equal and just, when in fact what happens, is an increase in the degree of resignation and acceptance towards diversity and subtle forms of injustice and exploitation. The results refer to strategies for entering higher education of discriminated social and ethnic-racial segments are a way to minimize the exclusion process that Brazil has faced since the discovery. However, it is assumed that such affirmative actions must be complemented with educational actions that strengthen access to knowledge. The perspective of Affirmative Actions in higher education should not only increase the access of blacks, indigenous people and public school graduates, but also, their permanence and integration. In addition, the results remind about the Indian, to enter /to stay /to complete a university. That has as central characteristics to be monolingual, hierarchical, Eurocentric or North American-centric; it is not a simple process, because the contradictions exist among the intercultural intentions of a logic marked by exclusion, competition and selection, and the perspective of a public and democratic university, which has not yet become intercultural. However, the specific Entrance Examination allowed reflections on what changes are possible, with the insertion and promotion of new processes and protagonism of students and indigenous leaderships.